Finite Element Modeling and Analysis of High Power, Low-loss Flux-Pipe Resonant Coils for Static Bidirectional Wireless Power Transfer - Babatunde Olukotun; Julius Partridge; Richard Bucknall (Energies, 2019)
This paper presents the optimal modeling and finite element analysis of strong-coupled, high-power and low-loss flux-pipe resonant coils for bidirectional wireless power transfer (WPT), applicable to electric vehicles (EVs) using series-series compensation topology. The initial design involves the modeling of strong-coupled flux-pipe coils with a fixed number of wire-turns. The ohmic and core loss reduction for the optimized coil model was implemented by creating two separate coils that are electrically parallel but magnetically coupled in order to achieve maximum flux linkage between the secondary and primary coils. Reduction in the magnitude of eddy current losses was realized by design modification of the ferrite core geometry and optimized selection of shielding material. The ferrite core geometry was modified to create a C-shape that enabled the boosting and linkage of useful magnetic flux. In addition, an alternative copper shielding methodology was selected with the advantage of having fewer eddy current power losses per unit mass when compared with aluminum of the same physical dimension. From the simulation results obtained, the proposed flux-pipe model offers higher coil-to-coil efficiency and a significant increase in power level when compared with equivalent circular, rectangular and traditional flux-pipe models over a range of load resistance. The proposed model design is capable of transferring over 11 kW of power across an airgap of 200 mm with a coil-to-coil efficiency of over 99% at a load resistance of 60 Ω.